2019
DOI: 10.1111/jsbm.12499
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Taking Action to Start a New Business

Abstract: Mindfulness, meaning a receptive attention to and awareness of present events and experience, is reported to have a wide range of benefits, but it has been suggested that it could prove costly in term s of task performance. This article analyzes how dispositional mindfulness relates to taking entrepreneurial action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…In traditional business, previous studies have demonstrated a link between MFN and start-up intention (Caliendo et al, 2014;Frese & Gielnik, 2014;Gelderen et al, 2019;Rerup, 2005). Although, Gelderen et al (2019) declare that individuals with lower levels of mindfulness were more likely to take entrepreneurial action than higher mindful ones, but they also found that individuals with a high level of mindfulness when they have decided to start a business will take more action, even more drastic, if they have business experience. This also makes sense when explaining SEI as entrepreneurs must have consideration and understanding before deciding to enter this field.…”
Section: Mindfulnessmentioning
confidence: 93%
See 1 more Smart Citation
“…In traditional business, previous studies have demonstrated a link between MFN and start-up intention (Caliendo et al, 2014;Frese & Gielnik, 2014;Gelderen et al, 2019;Rerup, 2005). Although, Gelderen et al (2019) declare that individuals with lower levels of mindfulness were more likely to take entrepreneurial action than higher mindful ones, but they also found that individuals with a high level of mindfulness when they have decided to start a business will take more action, even more drastic, if they have business experience. This also makes sense when explaining SEI as entrepreneurs must have consideration and understanding before deciding to enter this field.…”
Section: Mindfulnessmentioning
confidence: 93%
“…In entrepreneurship, MFN can help explain how entrepreneurs anticipate and take advantage of opportunities that others may not (Capel, 2014;Rerup, 2005). High levels of MFN can promote entrepreneurial behaviour through increased flexibility in awareness of situations (Gelderen et al, 2019). These are the important prerequisites for an individual to increase SEI.…”
Section: Mindfulnessmentioning
confidence: 99%
“…Indeed, meditation is a broad umbrella term that can refer to different contemplative practices (e.g., mindfulness meditation, LKM, visualization meditation; see Dahl et al (2015) for a detailed review and classification). Another form of meditation, mindfulness, has seen increasing popularity in research, including in management and entrepreneurship (e.g., Good et al, 2016; Kudesia, 2019; Murnieks et al, 2019; van Gelderen et al, 2019), and in the popular press (e.g., Gelles, 2018) where it is sometimes used interchangeably with the larger concept of meditation. To avoid confusion, our specific focus in this study is on LKM.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In this regard, we recommend future research to explore the pathways through which HSPs can flourish in entrepreneurship. It may be interesting to consider mindfulness (Van Gelderen, Kibler, Kautonen, Munoz, & Wincent, 2018) as the link between SPS and entrepreneurial action, as well as the interplay of inhibition-SPS versus disinhibition/impulsivity-ETP (Lerner, Hatak, & Rauch, 2018) for entrepreneurial action, adding to the emerging conversation on logics of entrepreneurship (Lerner, Hunt, & Dimov, 2018).…”
Section: Discussionmentioning
confidence: 99%